Kinetics of the Interactions between Copper and Amyloid‐β with FAD Mutations and Phosphorylation at the N terminus. (2nd August 2016) - Girvan, Paul; Miyake, Toru; Teng, Xiangyu; Branch, Thomas; Ying, Liming
Abstract: Mutations and post‐translational modifications of amyloid‐β (Aβ) peptide in its N terminus have been shown to increase fibril formation, yet the molecular mechanism is not clear. Here we investigated the kinetics of the interactions of copper with two Aβ peptides containing Familial Alzheimer's disease (FAD) mutations (English (H6R) and Tottori (D7N)), as well as with Aβ peptide phosphorylated at serine 8 (pS8). All three peptides bind to copper with a similar rate as the wild‐type (wt). The dissociation rates follow the order pS8>H6R>wt>D7N; the interconversion between the two coordinating species occurs 50 % faster for H6R and pS8, whereas D7N had only a negligible effect. Interestingly, the rate of ternary complex (copper‐bridged heterodimer) formation for the modified peptides was significantly faster than that for wt, thus leading us to propose that FAD and sporadic AD might share a kinetic origin for the enhanced oligomerisation of Aβ. Abstract : Metal‐bridged dimer correlates with AD : Two FAD mutations (H6R, English and D7N, Tottori) and phosphorylation at Ser8 of amyloid‐β peptide modulate the kinetics of interconversion between the two coordination modes and enhance copper‐bridged dimer formation, but with little impact on the copper binding rate constant.